(3GdfaS GdjeGfi hGdQhM GdQjMGfi aj ELGRI GdbVGI Hfi GdThcGfis - (3YHO GdQMef Hf SdjeGf Hf jMji GHf YeQ ebHhd GdCgOd, GdMSjfj GdWGdHj,J (B1250 (3g` s ((3eMeO Hf CMeO Hf YHOGddg s)
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ ddg eG TGAGddg hdGbhI EdG HGddg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B140s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B326 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs